Ketahanan Ekonomi Single Parent Kaum Perempuan Kabupaten Bengkayang - Rahmah, Safira Nur; Verdianti, Verdianti; Jannah, Syamratun Nur (Studia Economica : Jurnal Ekonomi Islam, 2024)
The purpose of this writing is to determine: 1) the economic conditions of female single parent families in Gerantung Village, Monterado District, Bengkayang Regency. 2) the efforts of single parents by women to fulfill the family's economic requirements in Gerantung Village, Monterado District, Bengkayang Regency. 3) the important role of women's single parents in the family in Gerantung Village, Monterado District, Bengkayang Regency. For the purposes of presenting data, researchers use a descriptive type, namely research that attempts to describe or interpret objects according to what they are or a research strategy in which the researcher investigates events, phenomena in the lives of individuals and asks a person or group of individuals to tell about their lives. Thus, it can be explained that the economic conditions of women's single parent families in Gerantung Village, Monterado District, Regency fall into several categories, namely Pre-Prosperous Families, Prosperous Families I, Prosperous Families II and Prosperous Families III. As well as the efforts of single parents by women to fulfill the family economy in Gerantung Village, Monterado District, Bengkayang Regency, they are very diverse and the important role of single parent women in the family. In Gerantung Village, Monterado District, Bengkayang Regency, of course the role played by single parent women is important, they must play a role. as father and mother to their children. Therefore, this research tries to reveal the struggles of single parents, especially women, even though many people look down on them, but in reality they are very great and extraordinary women